The implication of house price towards real estate investment trust return in Malaysia / Norazlina Samin - Samin, Norazlina (2007)
The hedging benefits of Real Estate Investment Trust (REIT) during inflation and inflation makes REITs become more favorable and popular among Malaysian investors lately. The implications of real estate towards Real Estate Investment Trust (REITs) return have been argued by past researcher. Thus, the questioned rise whether the increase or decrease of Malaysian House Price has a significant impact towards Real Estate Investment Trust return in Malaysia. The statistical tool used in this study is Correlation and Regression Method. As a proxy to Real Estate Investment Trust (REITs), this study is using REITs return. This study determines the changes in price of terraced house, apartment, detached, semi-detached house and Real Estate Investment Trust return. From the return of REIT and price change of house, the statistical test conducted by SPSS and estimated statistical model to examine the significant. The previous researchers have found that there are positive relationships between both variables and some finding of past research says it don't have a relationship at all. They have a different empirical work such as even study and auto correlation. In a nutshell, this study can be use by the investors as their guideline when making an investment decision to invest in Real Estate Investment Trust.